Representational guidance and student engagement: examining designs for collaboration in online synchronous environments - Sullivan, Florence R.; Hamilton, Claire E.; Allessio, Danielle A.; Boit, Rachel J.; Deschamps, Alexandra D.; Sindelar, Tony; Ramos, German E. Vargas; Randall, Anthony; Wilson, Nicholas; Zhu, Yan (Educational technology research and development, 2011)
In this paper we report the results of a study which investigated the affordances of multi-user virtual environments (MUVEs) for collaborative learning from a design perspective. Utilizing a mixed methods approach, we conducted a comparative study of the effect of varying representational and interactional design features on a collaborative design activity in three online synchronous environments. We compared environments featuring multiple modes of interaction (MUVEs), shared representations (text chat and 2D still images) and text-only features. Sixty-one students enrolled in an undergraduate course on Child Development participated in the study. Participants were asked to design a theoretically-based, developmentally appropriate, preschool classroom setting. Students were randomly assigned to one of three online learning environments that provided varying levels of representation and interaction. Significant differences in collaborative problem solving interactions were found. Participants in the shared representations + text condition evidenced stronger learning outcomes as regards substantive discussion and integration of child development concepts; while participants in the MUVE condition reported the most enjoyment with the experience. These findings are explained by the concepts of representational guidance, representational bias, educational affordances and interface design metaphors. Suggestions for the design of MUVEs for collaborative learning are provided.